Three Phase Induction Motor Torque Ripple Minimization Based On a Novel Nonlinear Dynamic Inverse Controller - Keream, Settar S.; Abdalla, Ahmed N.; Frayyeh, Hatem Fahad; Mohd Razali, Daud (Universiti Malaysia Pahang, 2016)
A Nonlinear Dynamic Inverse (NDI) controller is proposed in this work to minimize the ripple torque based on space vector pulse width modulation (SVPWM) which is used in high power induction motors. The nonlinear dynamic inverse controller canceled a non-desirable response of the induction motor and enhancing the performance. This cancellation attempt by a carful nonlinear algebraic equations. First, a mathematical model of induction motor and linearization process were made decoupling between two inputs have achieved. Then the desired new dynamic are derived from implementing the proposed NDIC technique that reserves some benefits such as fast torque control, high torque at low speed, and fast speed response. Also, the proposed method greatly reduced the torque ripple which is the primary concerns of the classical hysteresis-based direct torque control (DTC) scheme and have an effect on the stator current distortion. The system stability with the designed (NDISVPWM) method is analyzed using the Lyapunov stability theory. Finally, the simulation results with MATLAB/Simulink achieved for a 50-HP IM drive. The results are verification proved that the proposed (NDI-SVPWM) system performs smaller torque ripple and faster torque response than the conventional SVM-based proportional plus integral (PI-DTC) method.